CT-06 Factors affecting the attitudes of patients with systemic lupus erythematosus regarding potential clinical trial participation. (31st August 2016) - McNaughton, E; Lops, S; Felicione, E; Wagner, C
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disorder affecting skin, joints, kidneys, brain and other organs. Clinical trial recruitment is especially challenging in this patient population. To address challenges of recruiting patients with SLE into clinical trials, we conducted a survey study to: (1) explore patients' satisfaction with their current treatment; (2) assess participants' motivations to switch to a new treatment; and (3) identify the characteristics of patients willing to participate in a clinical trial. Materials and methods: 259 members of an online patient network with SLE aged 18–77 (mean age = 47; 96% female, 78% white) completed an online survey about their experience and attitudes. Data was collected over 7 days. The Chi square test was used to analyse the distribution of categorical variables; two sample t-tests to compare group means, and Pearson r correlation to identify the associations between continuous variables. Results: 60% of SLE patients reported being at least "somewhat satisfied" with their current treatment; 74% name worsening symptoms as an important factor for changing medications. Those patients (36%) who were motivated to change to a new treatment reported a slightly more severe daily impact of SLE (mean = 3.6 on a scale 1: not at all – 5 very much) than patients who did not view new treatment availability as a reason to change their current medication (SLE impact mean = 3.3; t (258) = 2.49; p < 0.01). 29% say knowing that a trial drug has never been tested before will increase the likelihood of their participation in the trial. Correlation analyses revealed slight, but significant association between a favourable view of novel drug trials and higher number of treatments, frequency of healthcare utilisation, and lupus daily impact (r ranged 0.13 – 0.22, p < 0.03). Disease-related factors positively associated with interest in clinical trial participation are SLE daily impact (r = 0.26, p < 0.03), headaches (χ 2 = 14.06, p < 0.01), and pain (χ 2 = 8.8, p < 0.05); treatment-related factors are burden of treatment, frequency of flares, frequency of healthcare utilisation, number of medications (r ranged 0.14 – 0.18, p < 0.03), and use of pain medications (χ 2 = 12.6, p < 0.05). Conclusions: Investigators may achieve a higher recruitment rate by targeting: 1) patients whose SLE symptoms are under poor control and who therefore frequently utilise the healthcare system; and 2) those patients who are experiencing more pain and headaches and more frequently using pain medications.